Treatment Options to Reduce Disease Activity After Natalizumab: Paradoxical Effects of Corticosteroids. (19th May 2014) - Rossi, Silvia; Motta, Caterina; Studer, Valeria; Boffa, Laura; De Chiara, Valentina; Castelli, Maura; Barbieri, Francesca; Buttari, Fabio; Monteleone, Fabrizia; Germani, Giorgio; Macchiarulo, Giulia; Weiss, Sagit; et al.
Summary Aim Natalizumab (NTZ) discontinuation leads to multiple sclerosis (MS) recurrence, but represents the only known strategy to limit the risk of progressive multifocal leukoencephalopathy (PML) in JCV seropositive patients. Here, we compared the clinical and imaging features of three groups of patients who discontinued NTZ treatment. Methods We treated 25 patients with subcutaneous INFβ‐1b (INF group), 40 patients with glatiramer acetate (GA group), and 40 patients with GA plus pulse steroid (GA+CS group). Results Six of 25 patients (24%) of the INF group were relapse‐free 6 months after NTZ suspension. In GA group, a significant higher proportion of patients (26 of 40 patients, 65%) were relapse‐free (P < 0.05). Far from improving the clinical effects of GA in post‐NTZ setting, combination of GA+CS was associated with lower relapse‐free rate than GA alone (40% vs. 65%, P = 0.04). Also on MRI parameters, combination of GA+CS was associated with worse outcome than GA alone, as 22 of 26 subjects (84.6%) had MRI evidence of disease activity 6 months after NTZ discontinuation. Conclusion Corticosteroids should not be used in combination with GA to prevent post‐NTZ disease recurrence.